Composite diaphragm and preparation method thereof, battery, battery pack and electric equipment
By using a composite material layer in the battery separator, combining high-entropy porous ceramic materials and dense ceramic materials, the problem of short circuit and thermal runaway during thermal abuse, mechanical abuse and electrical abuse is solved, and the power battery is achieved higher mechanical strength and thermal stability are achieved, and the battery safety is improved.
Patent Information
- Application Number
- CN202411501193.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-25
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-10-25
AI Technical Summary
Power batteries are prone to short circuits and thermal runaway problems during thermal abuse, mechanical abuse and electrical abuse. The mechanical properties and thermal stability of existing diaphragm materials are insufficient, making it difficult to meet the requirements of battery safety.
A composite diaphragm is used, which consists of a base film and a composite material layer, which includes a high-entropy porous ceramic material and a dense ceramic material, and is prepared by a microgravure roller coating process to improve the mechanical strength and thermal stability of the diaphragm.
It improves the safety of the battery, enhances the mechanical strength and thermal stability of the diaphragm, extends the thermal runaway time of the battery, and reduces the generation of dust and foreign matter during battery assembly.
Smart Images

Figure BDA0005102881590000131
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of batteries, and in particular relates to a composite diaphragm and a preparation method thereof, a battery, a battery pack and electrical equipment. Background Art
[0002] The rapid development of new energy vehicles has put more and more urgent demands on the energy density of power batteries. As the energy density of power batteries continues to increase, while bringing longer battery life, the safety of power batteries has been challenged. In particular, when the battery undergoes thermal abuse, mechanical abuse, and electrical abuse, lithium-ion batteries are prone to positive and negative short circuits and thermal runaway problems. Among them, the mechanical properties and thermal stability of the diaphragm material are directly related to the safety of the battery. Therefore, providing a diaphragm with high mechanical strength and high thermal stability is a technical problem that needs to be solved in this field. Summary of the invention
[0003] The main purpose of the present invention is to provide a composite diaphragm, which has high mechanical strength and high thermal stability.
[0004] The present invention also provides a method for preparing the composite diaphragm, which can prepare the composite diaphragm and has simple process and low cost.
[0005] The present invention also provides a battery, comprising the composite diaphragm, so the battery has higher safety.
[0006] The present invention also provides a battery pack, comprising the above-mentioned battery, so the battery pack has higher safety.
[0007] The present invention also provides an electrical device, comprising the above-mentioned battery or battery pack, so the electrical device has higher safety.
[0008] In a first aspect, the present invention provides a composite diaphragm, comprising a base membrane and a composite material layer present on at least one surface of the base membrane, the composite material layer comprising a first ceramic material and a second ceramic material, the first ceramic material being a high entropy porous ceramic material containing at least 5 metal elements, and the second ceramic material being a ceramic material containing less than 5 metal elements.
[0009] As for the composite membrane as described above, the first ceramic material includes at least one of high entropy porous oxide ceramic material, high entropy porous carbide ceramic material, high entropy porous nitride ceramic material, high entropy porous boride ceramic material, and high entropy porous sulfide ceramic material, and is preferably a high entropy porous carbide ceramic material.
[0010] As described above, the first ceramic material comprises (Zr 0.2 Hf 0.2 Ti0.2 Nb 0.2 Ta 0.2 )C、(Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2 )N、(Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2 ) 、 (Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2 )B, preferably (Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2 )C.
[0011] In the composite diaphragm as described above, the second ceramic material includes at least one of boehmite, aluminum oxide, silicon oxide, titanium oxide, barium oxide, magnesium oxide, barium titanate, zirconium oxide, and magnesium hydroxide.
[0012] In the composite diaphragm as described above, the mass fraction of the first ceramic material to the sum of the mass of the first ceramic material and the second ceramic material is 5%-50%, preferably 15%-40%.
[0013] In the composite diaphragm as described above, the thickness of the composite material layer is 1 μm-3 μm, preferably 1.5 μm-3 μm.
[0014] The composite diaphragm as described above, wherein the D50 of the first ceramic material is 0.8 μm-2 μm, preferably 1.0 μm-1.6 μm;
[0015] And / or, the D50 of the second ceramic material is 0.2 μm-0.8 μm, preferably 0.3 μm-0.6 μm.
[0016] In a second aspect, the present invention provides a battery comprising the composite separator as described above.
[0017] In a third aspect, the present invention provides a battery pack, comprising the battery as described above.
[0018] In a fourth aspect, the present invention provides an electrical device, comprising the battery or the battery pack as described above.
[0019] The composite material layer in the composite membrane provided by the present invention includes a first ceramic material and a second ceramic material, which can not only take advantage of the second ceramic material's compactness and high compressive strength, but also take advantage of the first ceramic material's low thermal conductivity, low density and high porosity, thereby making the composite membrane have higher mechanical strength and higher thermal stability. When applied to batteries, the safety of the batteries can be improved. DETAILED DESCRIPTION
[0020] In order to make the purpose, technical solutions and advantages of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0021] Battery separators play a vital role in lithium-ion batteries, fuel cells and other energy storage devices. Their main function is to separate the positive and negative electrodes of the battery to prevent internal short circuits in the battery while allowing ions to pass through to complete electrochemical reactions. Therefore, the mechanical properties and thermal stability of the separator material are directly related to the safety of the battery.
[0022] The thermal runaway process of the battery is arranged from low temperature to high temperature. The lithium-ion power battery will experience the following processes in sequence: high-temperature capacity attenuation, SEI film decomposition, negative electrode-electrolyte reaction, diaphragm melting process, positive electrode decomposition reaction, electrolyte solution decomposition reaction, negative electrode and adhesive reaction, electrolyte combustion, etc.; the thermal runaway heat release of the battery usually starts with the decomposition of the negative electrode SEI film and the negative electrode-electrolyte reaction. As the temperature continues to rise, the heat is transferred to the diaphragm, and the diaphragm begins to melt and disintegrate. Subsequently, a short circuit occurs in the battery, releasing a large amount of heat, causing the battery temperature to rapidly increase from 170°C to 200°C or even higher, reaching the thermal runaway trigger point of the positive electrode active material.
[0023] Conventional PE and PP diaphragms are prone to shrinkage or puncture and rupture when heated due to their low melting temperature and poor mechanical strength, which can lead to direct contact and short circuit between the positive and negative electrodes, causing thermal runaway. In order to improve the safety performance of the diaphragm, conventional ceramic materials such as Al2O3 and boehmite are usually coated on both sides of the conventional diaphragm to improve the mechanical strength and thermal stability of the diaphragm. This solution has been widely used in various types of lithium-ion batteries, including power batteries and 3C batteries. However, the current conventional ceramic materials have a large specific surface area and poor adhesion to the diaphragm, so they are easy to fall off the diaphragm, resulting in dust and foreign matter during battery assembly and reduced mechanical strength; and the high thermal conductivity of conventional ceramic materials leads to easy transfer of battery heat. Once there is a local thermal micro-runaway point inside the battery, thermal runaway is easy to transfer, and the battery safety performance is reduced. Therefore, it is crucial to improve the mechanical strength and thermal stability of the diaphragm and extend the thermal runaway time of the battery to improve the safety of the battery.
[0024] Based on this, in the first aspect, the present invention provides a composite diaphragm, comprising a base membrane and a composite material layer present on at least one surface of the base membrane, the composite material layer comprising a first ceramic material and a second ceramic material, the first ceramic material being a high entropy porous ceramic material containing at least 5 metal elements, and the second ceramic material being a ceramic material containing less than 5 metal elements.
[0025] The composite material layer in the composite diaphragm of the present invention comprises a first ceramic material and a second ceramic material, so that the composite diaphragm has high mechanical strength and high thermal stability, and can be applied to batteries to improve the safety of the batteries.
[0026] The first ceramic material, that is, the multiple elements in the high-entropy porous ceramic material, can make the high-entropy porous ceramic material form a highly mixed solid solution structure, which can effectively enhance the tear resistance and puncture resistance of the composite diaphragm. The porous structure can provide good mechanical support, disperse stress, and prevent local stress concentration. The second ceramic material has high strength and high hardness, which can improve the mechanical strength and wear resistance of the composite diaphragm. The micron-level high-entropy porous ceramic material and the nano-level second ceramic material are filled and coated on the base film, which can significantly improve the bonding force and mechanical strength between the composite material layer and the base film, and avoid the coating shedding caused by the use of the nano-level second ceramic material alone. The use of the micron-level high-entropy porous ceramic material alone has a large number of micropores, and the coating has poor mechanical strength. The composite diaphragm can effectively avoid the risk of failure of the short-circuit detection (hi-pot) of the negative electrode pre-lithiation pole core battery, and improve the process yield and safety of the battery.
[0027] In addition, the first ceramic material usually has a lower thermal conductivity, which can maintain the stability of its structure and performance in a high temperature environment, and prevent the composite diaphragm from shrinking, melting or decomposing at high temperatures. Its porous structure can provide a certain thermal isolation effect, slowing down the conduction of heat in the composite diaphragm, thereby improving the stability of the composite diaphragm in a high temperature environment. The second ceramic material usually has a higher thermal conductivity, can transfer heat quickly, can maintain dimensional stability when the temperature changes, and prevent the diaphragm from deforming at high temperatures. During the thermal runaway process of the battery, the low thermal conductivity of the first ceramic material can effectively isolate the further expansion of the thermal runaway site, and in the middle and late stages of the thermal runaway spread, the high thermal conductivity of the second ceramic material can quickly transfer heat. Through this two-step protection, the safety performance of the battery can be improved.
[0028] In addition, due to the presence of a large number of micropores in the first ceramic material, the air permeability of the composite diaphragm can be significantly improved, while storing more electrolyte, thus avoiding the problem of decreased rate performance due to the over-density of the second ceramic material. The nano-scale second ceramic material is effectively filled in the gaps between the micron-scale first ceramic material, and the particles are stacked more densely, which can avoid the problems of high mass proportion of the diaphragm coating and insufficient lightweight of the diaphragm when the second ceramic material is used alone; at the same time, it can avoid the shortcomings of loose filling and low volume density of the diaphragm when the first ceramic material is used alone. While achieving lightweight diaphragm, the higher thermal stability of the first ceramic material is utilized to further improve the thermal stability of the composite material layer, effectively preventing the composite diaphragm from shrinking and melting under thermal runaway conditions.
[0029] It can be understood that high entropy ceramic materials generally refer to ceramic materials with a simple crystal structure composed of five or more metal elements and one non-metallic element. High entropy porous ceramic materials, i.e., the first ceramic material, are porous high entropy ceramic materials prepared by in-situ reaction of gas release on the basis of high entropy ceramic materials. Compared with ceramic materials with less than 5 metal elements, i.e., the second ceramic material, high entropy porous ceramic materials have excellent properties such as low thermal conductivity, low density, and high porosity. The particle size is relatively larger than that of the second ceramic material, generally in the micron level, and has good compressibility. The second ceramic material is usually nanometer-level.
[0030] The present invention does not limit the specific type of the base film, and the separator conventionally used in the art, such as PP film, PE film, PVDF film, etc., can be used.
[0031] The composite material layer in the composite membrane provided by the present invention includes a first ceramic material and a second ceramic material, which can not only take advantage of the second ceramic material's compactness and high compressive strength, but also take advantage of the first ceramic material's low thermal conductivity, low density and high porosity, thereby making the composite membrane have higher mechanical strength and higher thermal stability. When applied to batteries, the safety of the batteries can be improved.
[0032] The method for preparing the composite diaphragm of the present invention may include the following steps:
[0033] The first ceramic material and the second ceramic material are coated on the base film by a micro-gravure roller coating process to obtain a composite diaphragm.
[0034] The preparation method of the composite diaphragm of the present invention adopts a micro-gravure roller coating process, which may specifically include the following steps:
[0035] 1) Adding the first ceramic material, the second ceramic material, the binder and the dispersant into water in sequence, stirring and dispersing the components in the water evenly, and obtaining a stable composite material slurry.
[0036] 2) Using a micro gravure roller, the composite material slurry prepared in step 1) is evenly coated on the polymer base film (it can be coated on one side or both sides of the base film) to obtain a composite diaphragm precursor. According to the viscosity and solid content of the composite material slurry, the operating parameters of the micro gravure roller are adjusted to meet the requirements of the coating thickness and surface density of the composite material layer.
[0037] 3) Drying the composite diaphragm precursor to obtain the composite diaphragm.
[0038] It can be understood that the so-called micro in micro gravure roller means that the diameter of the anilox roller is smaller than that of the traditional anilox roller. The diameter of the traditional anilox roller that is widely used now is usually 125mm-250mm. The diameter of the micro gravure roller is usually only 20mm-50mm. The selection of the roller diameter depends largely on the width of the coating. In the case of wider coating, to ensure the strength and straightness of the roller, it is necessary to select a roller with a larger diameter. For example, a 20mm diameter roller can be selected for a coating of 300mm width, and a 50mm roller can be selected for a coating of 1.6m width. The smaller the diameter of the roller, the smaller the contact line between the substrate and the roller. When the contact line is smaller, the possibility of coating defects will be smaller.
[0039] The preparation method of the composite diaphragm in the present invention adopts a micro-gravure roller coating process to prepare the composite diaphragm of the present invention. The preparation method is simple and easy with low cost. The composite diaphragm has high mechanical strength and high thermal stability. It is applied to batteries to improve the safety of the batteries.
[0040] In some embodiments of the present invention, the line count of the micro gravure roller in the micro gravure roller coating process is 100 lines / cm-200 lines / cm, the line depth is 20μm-90μm, the coating speed is 20m / min-60m / min, and the speed ratio is 90%-120%.
[0041] Exemplarily, the number of lines of the micro gravure roller in the micro gravure roller coating process can be 100 lines / cm, 110 lines / cm, 120 lines / cm, 130 lines / cm, 140 lines / cm, 150 lines / cm, 160 lines / cm, 170 lines / cm, 180 lines / cm, 190 lines / cm, 200 lines / cm or any two of them. The line depth can be 20μm, 30μm, 40μm, 50μm, 60μm, 70μm, 80μm, 90μm or any two of them. The coating speed can be 20m / min, 30m / min, 40m / min, 50m / min, 60m / min or any two of them. The speed ratio can be 90%, 95%, 100%, 105%, 110%, 115%, 120% or any two of them.
[0042] It can be understood that the speed ratio refers to the ratio of the running speed of the micro-gravure roller to the running speed of the base film belt.
[0043] The number of lines of the micro-gravure roller in the micro-gravure roller coating process of the present invention is within the above range, which can provide a higher resolution, make the coating more uniform and smooth, and provide a higher coating efficiency while ensuring the coating quality.
[0044] The line depth of the micro-gravure roller in the micro-gravure roller coating process of the present invention is within the above range, which can ensure that the first ceramic material and the second ceramic material are evenly distributed on the surface of the base film and avoid stripes, spots or other uneven phenomena.
[0045] The coating speed of the micro gravure roller in the micro gravure roller coating process of the present invention is within the above range, which can improve production efficiency.
[0046] The speed ratio in the micro-gravure roller coating process of the present invention is within the above range, which can ensure the speed matching between the coating roller and the base film, optimize the coating thickness and uniformity, and the coating process is relatively stable, avoiding uneven coating or shedding of the coating layer, thereby improving the consistency and reliability of the coating.
[0047] In some embodiments, the first ceramic material includes at least one of a high entropy porous oxide ceramic material, a high entropy porous carbide ceramic material, a high entropy porous nitride ceramic material, a high entropy porous boride ceramic material, and a high entropy porous sulfide ceramic material, preferably a high entropy porous carbide ceramic material. Specifically, the first ceramic material includes (Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2 )C、(Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2Ta 0.2 )N、(Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2 ) 、 (Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2 )B, preferably (Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2 )C.
[0048] Because the above-mentioned first ceramic material has a low thermal conductivity and can maintain stable physical and chemical properties at high temperatures, the thermal stability of the composite membrane can be further improved; and because the above-mentioned ceramic material has a high porosity, the air permeability of the composite membrane can be improved, more electrolyte can be stored, and the composite membrane can also be made lightweight.
[0049] In some embodiments of the present invention, the second ceramic material includes at least one of boehmite, aluminum oxide, silicon oxide, titanium oxide, barium oxide, magnesium oxide, barium titanate, zirconium oxide, and magnesium hydroxide.
[0050] The second ceramic material has a high density and high mechanical strength, which can further improve the mechanical strength of the composite diaphragm; in addition, its high thermal conductivity can quickly transfer heat, thereby improving the safety of the battery.
[0051] In some embodiments of the present invention, the mass fraction of the first ceramic material to the sum of the mass of the first ceramic material and the second ceramic material is 5%-50%, preferably 15%-40%.
[0052] Exemplarily, the mass fraction of the first ceramic material to the sum of the mass of the first ceramic material and the second ceramic material may be 5%, 10%, 15%, 20%, 30%, 40%, 50% or a range consisting of any two thereof.
[0053] The mass fraction of the first ceramic material in the sum of the masses of the first ceramic material and the second ceramic material is within the above range, which helps to disperse stress and prevent local stress concentration, thereby further improving the overall mechanical strength of the composite diaphragm. And maintain a stable structure at high temperatures to prevent the composite diaphragm from shrinking, melting or decomposing at high temperatures. If the mass fraction of the first ceramic material in the sum of the masses of the first ceramic material and the second ceramic material is too low, the first ceramic material cannot give full play to its low thermal conductivity, low density, and high porosity, and play the advantages of absorbing and retaining liquid, being lightweight, and effectively preventing heat diffusion; if the mass fraction of the first ceramic material in the sum of the masses of the first ceramic material and the second ceramic material is too high, the density of the composite material layer will be reduced, the mechanical strength will decrease, and the heat transfer capacity will be poor after heat diffusion.
[0054] The present invention does not limit the testing method of the mass fraction of the first ceramic material in the sum of the masses of the first ceramic material and the second ceramic material. For example, the elements and component compositions may be detected by SEM-EDS surface scanning or XRD scanning.
[0055] In some embodiments of the present invention, the thickness of the composite material layer is 1 μm-3 μm, preferably 1.5 μm-3 μm.
[0056] For example, the thickness of the composite material layer may be 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm, or a range consisting of any two thereof.
[0057] It can be understood that the thickness of the composite material layer in the present invention refers to the single-side thickness of the composite material layer. When the composite material layer is coated on both surfaces of the base film, the thickness of the composite material layer on each surface is in the range of 1 μm-3 μm. The thickness of the composite material layer can be adjusted by changing the number of lines, line depth, coating speed, and speed ratio of the micro-gravure roller in the micro-gravure roller coating process.
[0058] The thickness of the composite material layer within the above range can provide sufficient mechanical support and significantly improve the tear resistance and puncture resistance of the composite diaphragm; it can also effectively disperse stress and prevent local stress concentration, thereby improving the overall mechanical strength and durability of the composite diaphragm. In addition, the thickness of the composite material layer within the above range can provide a good thermal isolation effect and slow down the conduction of heat in the composite diaphragm, thereby improving the stability of the composite diaphragm in a high temperature environment and preventing the composite diaphragm from shrinking, melting or decomposing at high temperatures. If the composite material layer is too thin, the safety performance is insufficient; if the composite material layer is too thick, it will hinder the transmission of lithium ions and reduce the energy density of the battery. The more preferred coating thickness is 1.5 to 2.5 um.
[0059] The present invention is not limited to the testing method of the composite material layer thickness, which can be measured, for example, by SEM cross-sectional scanning.
[0060] In some embodiments of the present invention, the D50 of the first ceramic material is 0.8 μm-2 μm, preferably 1.0 μm-1.6 μm;
[0061] In some embodiments, the D50 of the second ceramic material is 0.2 μm-0.8 μm, preferably 0.3 μm-0.6 μm.
[0062] For example, the D50 of the first ceramic material may be 0.8 μm, 0.9 μm, 1 μm, 1.2 μm, 1.4 μm, 1.6 μm, 2 μm, or any two thereof. The D50 of the second ceramic material may be 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, or any two thereof.
[0063] In the present invention, the D50 of the first ceramic material and the D50 of the second ceramic material are within the above range, wherein the first ceramic material can provide a good mechanical reinforcement effect, and the second ceramic material helps to improve the mechanical strength and toughness of the composite material layer. The smaller D50 of the second ceramic material can be filled in the micropores of the first ceramic material, further enhancing the mechanical strength and toughness, and the smaller D50 of the second ceramic material is evenly distributed in the micropores of the first ceramic material, which can prevent stress concentration and improve the overall mechanical properties of the composite diaphragm.
[0064] The present invention does not limit the testing method of D50 of the first ceramic material and D50 of the second ceramic material. For example, they can be obtained by testing with a laser particle size analyzer.
[0065] In a third aspect, the present invention provides a battery, comprising the composite diaphragm as described above. The battery has the advantages corresponding to the above composite diaphragm, which will not be described in detail.
[0066] The battery of the present invention comprises a positive electrode sheet, a negative electrode sheet, an electrolyte and a shell in addition to the composite diaphragm, wherein the composite diaphragm is arranged between the positive electrode sheet and the negative electrode sheet.
[0067] The positive electrode sheet includes a positive electrode active material, a conductive agent and a binder. The positive electrode active material is selected from a ternary layered material, such as LiNi x Co y M (1-x-y) (M is Mn and / or Al), lithium-rich manganese-based material Li2MnO3·LiMO2 (M includes at least one of Ni, Co, and Mn), at least one of lithium cobalt oxide LiCoO2, preferably lithium nickel cobalt manganese oxide.
[0068] The negative electrode sheet includes a negative electrode active material, a conductive agent and a binder. The negative electrode active material is selected from at least one of silicon, tin, silicon oxide, tin oxide, a composite material of silicon and carbon, a composite material of tin and carbon, a silicon halide, a tin halide, a silicon alloy, and a tin alloy, and is preferably a graphite-doped silicon composite material. A pre-lithiation layer may be provided on the surface of the negative electrode sheet, the pre-lithiation layer includes lithium foil or lithium powder, and the pre-lithiation layer and the negative electrode sheet are rolled and composited to form a pre-lithiation negative electrode sheet.
[0069] The present invention does not particularly limit the specific types of the conductive agent and the adhesive. The conductive agent, the adhesive and other components can be selected from conventional materials in the field. For example, the conductive agent can be selected from one or more of conductive carbon black, carbon nanotubes, conductive graphite, and graphene, and the adhesive can be selected from one or more of polyvinylidene fluoride (PVDF), acrylic modified PVDF, polyacrylate polymers, polyimide, styrene-butadiene rubber, and styrene-propylene rubber.
[0070] In a fourth aspect, the present invention provides a battery pack, comprising the battery as described above. The battery pack has advantages corresponding to the above-mentioned composite diaphragm, which will not be described in detail.
[0071] In a fifth aspect, the present invention provides an electrical device, including the battery as described above or the battery pack as described above. The electrical device has advantages corresponding to the above-mentioned composite diaphragm, which will not be described in detail.
[0072] The electrical equipment of the present invention can be conventional electrical equipment in the field, such as power equipment (such as electric vehicles), electronic equipment (such as computers, mobile phones, digital cameras, printers, fax machines, etc.), wearable devices (such as watches, bracelets, VR glasses, etc.), household appliances (such as air conditioners, refrigerators, washing machines, microwave ovens, etc.), etc., without special restrictions.
[0073] The technical solution of the present invention is further described below in conjunction with specific embodiments.
[0074] Example 1
[0075] The method for preparing the battery cell of this embodiment comprises the following steps:
[0076] Composite diaphragm preparation:
[0077] 1) Add 15 parts by mass of the first ceramic material (Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2)C (D50 = 1.2 μm), 85 parts by mass of alumina powder of the second ceramic material (D50 = 0.5 μm), 270 parts by mass of pure water and 0.8 parts by mass of a dispersant (PVP-K30 model) are stirred and dispersed, and then 15 parts by mass of a binder (CM-1020 model) and 0.5 parts by mass of a wetting agent (Capstone FS-31 model) are added in sequence, stirred and dispersed evenly, and a stable composite material slurry is obtained.
[0078] 2) The composite material slurry is coated on both surfaces of a 9 μm thick PE microporous base membrane using a micro-gravure roller coating process, and the thickness of the composite material layer on each surface is 1.5 μm, to obtain a composite diaphragm precursor, wherein the line number of the micro-gravure roller is 150 lines / cm, the line depth is 40 μm, the coating speed is 40 m / min, and the speed ratio is 110%; the composite diaphragm precursor is dried to obtain a composite diaphragm.
[0079] Positive electrode preparation:
[0080] The ternary positive electrode active material NCM811, conductive carbon black Spuer_Li, and binder PVDF_5130 were mixed in N-methylpyrrolidone (NMP) at a mass ratio of 100:2:2.2, and then coated on the aluminum current collector, dried, rolled and die-cut into positive electrode sheets with a surface density of 440g / m 2 .
[0081] Negative electrode preparation:
[0082] Graphite, silicon-carbon material, CNT, and binder PAA were dissolved and mixed uniformly in deionized water at a mass ratio of 87:13:1.2:5 to prepare a negative electrode slurry, which was then coated on a copper foil. The density of the coated negative electrode active material layer on both sides was 198 g / m 2 , after roller pressing, it is made into a negative electrode sheet to be supplemented with lithium;
[0083] Pre-lithiation of negative electrode sheet: lithium powder is added to both sides of the negative electrode sheet to be supplemented, and the surface density of the supplemented lithium is 1.5g / m 2 , double-sided 3.0g / m 2 , to make a pre-lithiation negative electrode sheet.
[0084] Battery cell production:
[0085] The positive electrode sheet, composite separator, and pre-lithiation negative electrode sheet prepared above are stacked in sequence to make a 7+8-layer soft-pack battery with a rated capacity of 2450mAh.
[0086] Example 2
[0087] The preparation method of the battery cell of Example 2 is basically the same as that of Example 1, except that 40 parts by weight of the first ceramic material (Zr0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2 )C (D50=1.2μm), 60 parts by mass of alumina powder (D50=0.5μm), a second ceramic material.
[0088] Example 3
[0089] The preparation method of the battery cell of Example 3 is basically the same as that of Example 1, except that the line number of the micro-gravure roller is changed to 100 lines / cm, the line depth is 60 μm, and the thickness of the obtained composite material layer is 2.5 μm.
[0090] Example 4
[0091] The preparation methods of the battery cells of Example 4 and Example 2 are basically the same, except that the line number of the micro-gravure roller is changed to 100 lines / cm, the line depth is 60 μm, and the thickness of the composite material layer is obtained to be 2.5 μm.
[0092] Example 5
[0093] The preparation method of the battery cell of Example 5 is basically the same as that of Example 1, except that the first ceramic material is (Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2 )N(D50=2.0μm), the second ceramic material is boehmite, and D50 is 0.8μm.
[0094] Example 6
[0095] The preparation method of the battery cell of Example 6 is basically the same as that of Example 1, except that the first ceramic material is (Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2 )O (D50=0.8μm), the second ceramic material is boehmite, and D50 is 0.2μm.
[0096] Example 7
[0097] The preparation method of the battery cell of Example 7 is basically the same as that of Example 1, except that 5 parts by mass of the first ceramic material (Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2 )B (D50=1.2μm), 95 parts by mass of alumina powder (D50=0.5μm), a second ceramic material.
[0098] Example 8
[0099] The preparation method of the battery cell in Example 8 is basically the same as that in Example 1, except that 50 parts by weight of the first ceramic material (Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2 )C (D50=1.2μm), 50 parts by mass of alumina powder (D50=0.5μm), a second ceramic material.
[0100] Example 9
[0101] The preparation method of the battery cell of Example 9 is basically the same as that of Example 1, except that the line number of the micro-gravure roller is changed to 180 lines / cm, the line depth is 20 μm, and the thickness of the composite material layer is 1.0 μm.
[0102] Example 10
[0103] The preparation method of the battery cell of Example 10 is basically the same as that of Example 1, except that the line number of the micro-gravure roller is changed to 80 lines / cm, the line depth is 70 μm, and the thickness of the composite material layer is 3.0 μm.
[0104] Comparative Example 1
[0105] The preparation methods of the battery cells of Comparative Example 1 and Example 1 are basically the same, except that the first ceramic material is not added during the preparation of the composite material slurry, and 100 parts by mass of the second ceramic material alumina powder is added.
[0106] Comparative Example 2
[0107] The preparation methods of the battery cells of Comparative Example 2 and Example 1 are basically the same, except that, during the preparation of the composite material slurry, the second ceramic material alumina powder is not added, and 100 parts by mass of the first ceramic material are added.
[0108] Test example:
[0109] 1. D50: Take a 5 mm × 5 mm composite diaphragm for SEM-EDS surface observation, and use software to calculate the particle size distribution and particle size of the first ceramic material and the second ceramic material.
[0110] 2. Thickness of the composite material layer: Take a 5 mm × 5 mm composite diaphragm and perform ion cutting, and then perform SEM cross-section to test the thickness of the composite material layer.
[0111] 3. Air permeability test: Cut a 100mm×100mm composite diaphragm and use the American GURLEY-4110N tester with a pressure (water column height) of 12.39cm to measure the time (s / 100ml) required for 100ml of gas (air) to pass through the composite diaphragm. The smaller the value, the better the air permeability.
[0112] 4. Heat shrinkage test: Cut the composite diaphragm into a size of 120mm / 100mm according to the machine direction / transverse direction (MD / TD), cover the surface of the composite diaphragm with a piece of A4 paper, let it stand at 180℃ for 1 hour, measure the shrinkage of the composite diaphragm in each direction, and calculate the shrinkage ratio.
[0113] 5. Peel strength: Cut a 40mm×100mm composite diaphragm, fix the two sides of the composite diaphragm on the fixed fixture and the movable fixture respectively with tape, and reversely stretch it at 180°C to peel off the composite material layer and the base film. The greater the required pulling force, the higher the peel strength of the composite diaphragm.
[0114] 6. Hi-pot test: After lamination, the core is put into the hot press with 1.25Mpa pressure, and the hi-pot test is performed after 60s of hot pressing at 90℃. The hi-pot test voltage is U=300V, the voltage rise time t1=1s, the voltage holding time t2=5s, and the leakage current I=25uA. 100pcs of cores are measured continuously, and the hi-pot defect rate is calculated.
[0115] 7. Capacity test: First, fill the battery cell with liquid, age it and form it. Formation steps: charge at 0.05C for 2h, let it sit for 10min, charge at 0.2C for 3h, let it sit for 10min. Charge at 0.33C constant current and constant voltage to 4.3V, cut off at 0.05C, let it sit for 10min; discharge at 0.33C constant current to 2V, let it sit for 10min, repeat three times, use the third discharge capacity as the battery cell capacity, let it sit for 10min.
[0116] 8. Thermal runaway test: Use 0.33C CC-CV to charge to 4.3V, 0.05C to fully charge the battery. After leaving it for 30 minutes, place the battery in a temperature box. The temperature box is raised at a rate of 5℃ / min from room temperature to the temperature at which the battery voltage drops sharply and the battery produces gas. Record the temperature and elapsed time.
[0117] Table 1
[0118]
[0119] It can be seen from Table 1 that compared with the comparative example, the composite material layer in the composite membrane provided by the present invention includes a first ceramic material and a second ceramic material, which can not only give play to the advantages of the second ceramic material's density and high compressive strength, but also give play to the characteristics of the first ceramic material's low thermal conductivity, low density and high porosity, thereby making the composite membrane have higher mechanical strength and higher thermal stability, and can be applied to batteries to improve the safety of the batteries.
[0120] From the comparison between Example 1 and Comparative Examples 1-2, it can be seen that the composite diaphragm provided by the present invention has a lower thermal shrinkage ratio, a higher thermal runaway temperature, a longer duration from heating to thermal runaway, a lower Hi-pot failure rate, and a higher peel strength.
[0121] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A composite diaphragm, characterized in that: It includes a base film and a composite material layer present on at least one side of the base film, wherein the composite material layer includes a first ceramic material and a second ceramic material, wherein the first ceramic material is a high-entropy porous ceramic material containing at least 5 metal elements, and the second ceramic material is a ceramic material containing less than 5 metal elements.
2. The composite diaphragm according to claim 1, characterized in that: The first ceramic material includes at least one of a high entropy porous oxide ceramic material, a high entropy porous carbide ceramic material, a high entropy porous nitride ceramic material, a high entropy porous boride ceramic material, and a high entropy porous sulfide ceramic material, preferably a high entropy porous carbide ceramic material.
3. The composite diaphragm according to claim 2, characterized in that: The first ceramic material includes (Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2 )C、(Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2 )N、(Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2 )O、(Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2 )B, preferably (Zr 0.2 Hf 0.2 Ti 0.2 Nb 0.2 Ta 0.2 )C.
4. The composite diaphragm according to any one of claims 1 to 3, characterized in that: The second ceramic material includes at least one of boehmite, aluminum oxide, silicon oxide, titanium oxide, barium oxide, magnesium oxide, barium titanate, zirconium oxide, and magnesium hydroxide.
5. The composite diaphragm according to any one of claims 1 to 4, characterized in that: The mass fraction of the first ceramic material to the sum of the mass of the first ceramic material and the second ceramic material is 5%-50%, preferably 15%-40%.
6. The composite diaphragm according to any one of claims 1 to 5, characterized in that: The thickness of the composite material layer is 1 μm-3 μm, preferably 1.5 μm-3 μm.
7. The composite diaphragm according to any one of claims 1 to 6, characterized in that: The D50 of the first ceramic material is 0.8 μm-2 μm, preferably 1.0 μm-1.6 μm; And / or, the D50 of the second ceramic material is 0.2 μm-0.8 μm, preferably 0.3 μm-0.6 μm.
8. A battery, characterized in that: The composite diaphragm comprises the composite diaphragm according to any one of claims 1 to 7.
9. A battery pack, characterized in that: Comprising the battery as claimed in claim 8.
10. An electrical device, characterized in that: Comprising the battery according to claim 8 or the battery pack according to claim 9.
Citation Information
Patent Citations
High-entropy carbide ceramic with multi-scale pore structure and preparation method of high-entropy carbide ceramic
CN115385692A
Coating slurry, battery diaphragm and preparation method
CN117239353A
Preparation method of high-entropy monatomic catalyst modified diaphragm and application of high-entropy monatomic catalyst modified diaphragm in lithium-sulfur battery
CN117335094A
Preparation method of high-thermal-stability ceramic coated polyolefin diaphragm
CN117559078A
High-entropy ceramic-based composite material and preparation method thereof
CN117567158A